La produzione dell'antiziganismo nei discorsi dei politici dell'Italia contemporanea - Pontrandolfo, Stefania; Rizzin, Eva (Antropologia Pubblica, 2024)
Anti-Gypsyism can be contrasted, but it must first be unveiled, identified and described. The lack of elaboration of anti-Gypsyism as a particular form of racism allows it to persist, to be constantly and uncritically reproduced, not only in the common sense and by the media, but also in political and institutional discourses and actions, and in taxonomies and practices of state bureaucracy. The aim of this article is to reflect on the weight of Italian politicians hate speech in the construction of everyday anti-Gypsyism, to contribute in unveiling, deconstructing and contrasting it.